A systematic review of methods used to sample and analyse periradicular tissue fluid during root canal treatment. (27th March 2019) - Virdee, S. S.; Butt, K.; Grant, M.; Camilleri, J.; Cooper, P. R.; Tomson, P. L.
Abstract: Aim: The primary aim was to identify techniques used to sample and analyse periradicular tissue fluid (PTF) in permanent teeth diagnosed with apical disease during root canal treatment. Secondly, to identify the types of inflammatory mediators studied using this approach. Methodology: Data Sources: PubMed, EMBASE, Cochrane Library, Science Direct, Web of Science and OpenGrey. Eligibility Criteria : Clinical studies published until 1 June 2018 which utilized orthograde techniques to sample and analyse PTF were included. Cell culture, laboratory or animal studies and those concerned with investigating inflammatory mediator activity from within healthy or diseased pulp tissue, and not periradicular tissues, were excluded. Study appraisal and methods: In accordance with PRISMA guidelines, data were extracted on study characteristics, target mediators, sampling and assay techniques and the parameters associated with the PTF sampling and eluting protocol. A qualitative synthesis was conducted, and studies were critically appraised using a modified version of the Cochrane risk of bias tool. Results: Study Characteristics: From 251 studies, 33 were eligible for inclusion. Sampling techniques included the use of paper points ( n = 27), fine needle aspiration ( n = 4) and filter strips ( n = 2). Assay techniques included enzyme‐linked immunosorbent assay ( n = 18), quantitative polymerase chain reaction ( n = 9), radioimmunoassay ( n = 4), colorimetric assay ( n = 2), immunofluorometric assay ( n = 1) and cytometric bead array ( n = 1). Forty‐five different inflammatory mediators were targeted at the proteomic/metabolomic ( n = 25) or transcriptomic level ( n = 9). Limitations: Significant heterogeneity exists within the methodology, and only 5 studies disclosed unambiguous information about their PTF sampling and eluting protocols. Conclusions: Paper points and proteomic/metabolomic analysis are currently the preferred methods for studying and analysing PTF during root canal treatment. The most studied analytes were IL‐1β and TNF‐α. Implications: Further research is required to develop an optimized PTF sampling and eluting protocol to overcome methodological heterogeneity, and future studies are advised to follow a standardized approach to reporting their methodology.